2021
DOI: 10.3389/ffgc.2021.667151
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-2 Analysis of Spruce Crown Transparency Levels and Their Environmental Drivers After Summer Drought in the Northern Eifel (Germany)

Abstract: Droughts in recent years weaken the forest stands in Central Europe, where especially the spruce suffers from an increase in defoliation and mortality. Forest surveys monitor this trend based on sample trees at the local scale, whereas earth observation is able to provide area-wide information. With freely available cloud computing infrastructures such as Google Earth Engine, access to satellite data and high-performance computing resources has become straightforward. In this study, a simple approach for suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The stands are located between 390 and 525 m a.s.l., representing a shallow elevation gradient. This area was severely affected by the European heatwave in 2018, resulting in trees affected by extremely dry conditions and subsequent bark beetle infestations (Montzka et al 2021;Obladen et al 2021;Spiecker & Kahle 2023).…”
Section: Study Site Plant Materials and Phenotypic Characterizationmentioning
confidence: 99%
“…The stands are located between 390 and 525 m a.s.l., representing a shallow elevation gradient. This area was severely affected by the European heatwave in 2018, resulting in trees affected by extremely dry conditions and subsequent bark beetle infestations (Montzka et al 2021;Obladen et al 2021;Spiecker & Kahle 2023).…”
Section: Study Site Plant Materials and Phenotypic Characterizationmentioning
confidence: 99%
“…Large parts of the slopes and the upper parts of the Urft catchment are covered by broad-leaved and coniferous forests (Figure 3, Table S1) (Corine Landcover, 2018). The coniferous forest mainly consists of spruce which was introduced in the area in the 19th century (Montzka et al, 2021). Less inclined areas are used as pastures and for agriculture.…”
Section: Study Areamentioning
confidence: 99%
“…Multiple large-scale studies demonstrated the accurate assessment of forest disturbance and recovery [23,24]. Recent studies integrating optical imagery confirm drought-induced declines in forest health [25,26]. In particular, the analysis of products combining different remote sensing sensors at high spatial and temporal scale (e.g., Sentinel-1, Sentinel-2, Landsat) have gained in importance and popularity in institutional monitoring systems [12,23,27,28].…”
Section: Introductionmentioning
confidence: 99%